2009
DOI: 10.2151/jmsj.87.895
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Improved Turbulence Closure Model for the Atmospheric Boundary Layer

Abstract: An improved Mellor-Yamada (MY) turbulence closure model (MYNN model: Mellor-YamadaNakanishi-Niino model) that we have developed is summarized and its performance is demonstrated against a large-eddy simulation (LES) of a convective boundary layer. Unlike the original MY model, the MYNN model considers e¤ects of buoyancy on pressure covariances and e¤ects of stability on the turbulent length scale, with model constants determined from a LES database. One-dimensional simulations of Day 33 of the Wangara field ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
447
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 798 publications
(505 citation statements)
references
References 48 publications
4
447
0
Order By: Relevance
“…Rapid Radiative Transfer Model for GCMs (Iacono et al, 2008) Rapid Radiative Transfer Model for GCMs (Iacono et al, 2008) Dudhia (Dudhia, 1989) Boundary layer Yonsei University (Hong et al, 2006) Mellor-Yamada-Nakanishi-Niino (Nakanishi and Niino, 2009) Mellor-Yamada-Nakanishi-Niino (Nakanishi and Niino, 2009 Kain, 2004) previous studies focused on winter precipitation events in California, for which WRF has been more thoroughly tested than fire weather conditions (e.g. Caldwell et al, 2009;Chin et al, 2010;Smith et al, 2010;Dulière et al, 2011).…”
Section: Methodology: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid Radiative Transfer Model for GCMs (Iacono et al, 2008) Rapid Radiative Transfer Model for GCMs (Iacono et al, 2008) Dudhia (Dudhia, 1989) Boundary layer Yonsei University (Hong et al, 2006) Mellor-Yamada-Nakanishi-Niino (Nakanishi and Niino, 2009) Mellor-Yamada-Nakanishi-Niino (Nakanishi and Niino, 2009 Kain, 2004) previous studies focused on winter precipitation events in California, for which WRF has been more thoroughly tested than fire weather conditions (e.g. Caldwell et al, 2009;Chin et al, 2010;Smith et al, 2010;Dulière et al, 2011).…”
Section: Methodology: Model Configurationmentioning
confidence: 99%
“…Since the focus of this study is on dry conditions, we tested two additional configurations. Model configuration-2 (WRF-2) is a sensitivity test for which we replaced the boundary layer configuration used in WRF-1 with Mellor-Yamada-Nakanishi-Niino (MYNN; Nakanishi and Niino, 2009). Previous studies evaluating WRF performance in Southern California have identified PBL schemes as a primary source of error (Huang et al, 2013;Scarino et al, 2014).…”
Section: Methodology: Model Configurationmentioning
confidence: 99%
“…1), and 31 vertically staggered layers based on a terrain-following pressure coordinate system. The Mellor-Yamada-NakanishiNiino level 2.5 (MYNN; Nakanishi and Niino, 2009) is chosen as the planetary boundary scheme in this study. By using a vertical coordinate that is stretched to have higher resolutions inside the planetary boundary layer, the model has about 4-5 vertical layers inside the planetary boundary layer with a vertical resolution of ∼ 30 m near the surface.…”
Section: The Modelmentioning
confidence: 99%
“…The friction velocity is obtained with the Charnock formula. The model simulations were run with the MYNN 1.5-order level 2.5 PBL scheme (Nakanishi and Niino, 2009), on which the WRF-WF scheme is dependent. These and other details of the model configuration are summarised in Table 2.…”
Section: Wrf Model Configuration and Averagingmentioning
confidence: 99%